Hubungan Praktik Kerja Lapangan Dengan Minat Mahasiswa Pendidikan Tata Rias Dalam Berwirausaha Wedding Organizer - Loveia, Zahra Nabila; Irtawidjajanti, Sri; Jubaedah, Lilis (Jurnal Ilmiah Wahana Pendidikan, 2023)
Field Work Practice (PKL) can be interpreted as an activity to develop oneself and prepare a person to face the world of work. Street vendors indirectly provide knowledge and experience related to factors in entrepreneurship. The experience of street vendors that have been obtained by students is expected to be able to foster an interest in entrepreneurship. This study aims to determine whether there is a relationship between field work practices and the interest of students of Cosmetology Education at the State University of Jakarta in entrepreneurship as a wedding organizer. The method used in this study is a quantitative research method and uses a correlational research type. Based on the test results, it was found that the significance value was 0.0000 ± 0.05 so that the data was said to be correlated. The Pearson correlation value is 0.642 so it can be concluded that there is a positive and strong relationship. Based on the results of the t test, it shows that the significance value of the relationship between street vendors (X) and interest in Entrepreneurial Wedding Organizer (Y) is 0.000 ± 0.05 and the value of t count is 6.642, the value of t table is 1.997, so Ho is rejected and Ha is accepted. Based on the data obtained and the analysis carried out in this study, it can be concluded that there is a positive relationship between the experience of Field Work Practices (PKL) and the Interests of Makeup Education Students in Entrepreneurial Wedding Organizers.